58 Can Volunteers Improve the Well-Being, Participation and Activity of Patients on An Acute Older-Persons' Unit in Hospital?. (6th February 2020) - Jacob, C; Roff, K; Fleet, J; Jones, J; Wood, C A; Jensen, H; Allen, S; Bryan, A; Romero, D; Ray, L; Meldrum, T; Owen, B
Abstract: Background: A multi-disciplinary led, charity-funded initiative was implemented to deliver an Activity Promotion Project (APP) on the older adult wards of a large teaching hospital, providing acute medical management for adults over 65 with complex needs. Introduction: Previous local studies show that our patients are inactive, lonely and their activity is inhibited by ward culture. Cognitively impaired patients experiencing long delays for placement are often agitated and restless. Staff feel disheartened by their inability to spare time for non-medical needs. To respond to the Social Prescribing directive the APP aims to create a sustainable volunteer team to provide patients with company, stimulation and opportunities to be active. Methods: A Volunteer and Activity Coordinator (VAC) was appointed to recruit, train and coordinate applicants for the volunteer role on the unit which is advertised on the trust website. Analysis of volunteer team impact has been through patient, carer and staff surveys. Observational studies recorded patients' physical position, activity and company as well as use of the dayrooms before and during the project. Interventions: Patients of all functional abilities can be referred by any staff member. Individual and group activities include conversation, games, reminiscence quizzes, lunch and tea parties, musical bingo, walking tours, trips to hospital facilities and gardens and visits from therapy dogs and musicians. Before discharge participating patients are given information about local social and exercise opportunities. Results: All staff surveyed would recommend the project to colleagues, 97% thought it improved patient mood. One noted: 'volunteers have created a new energy on the ward, the patients appear to be much more engaged and occupied, and the dayroom is being used as it is intended to be'. Observational data showed a change in the percentage of patients resting in bed from 59% before the intervention to 49% during and a decrease in patients who were alone from 83% to 60%. Conclusions: The volunteer team has had a positive effect on ward culture and patient well-being and could be replicated in other ward settings. The programme's impact is contingent on the consistency and reliability of volunteers, which makes the role of the VAC essential for careful management and communication of clear expectations. The VAC role will be proposed in business planning for next financial year.